TRI UPASTAMBHA: FORMULASI PENGUAT KESEHATAN DI ERA NEW NORMAL : (Perspektif Ayurveda) - Arsana, Made (UHN IGB Sugriwa Denpasar, 2023)
The Covid-19 pandemic has triggered various complex problems in human life, so preventive measures are needed to break the chain of spread. Currently, it has entered the new normal era which is a new habit after being hit by a pandemic. Maintaining health remains one of the important actions that must be cultivated in order to prevent the spread of Covid 19, even in new habits. This paper analyzes Tri Upastambha as a health booster formulation in an Ayurvedic perspective, which can be a solution to maintain health stability in the Covid 19 era. The data in this paper was collected by observation, interview, and literature study techniques. Conceptually, Tri Upastambha is the three main pillars that can be used as habitus to strengthen health in the Ayurvedic view, namely, Ahara, Nidra, and Brahmacharya. Ahara emphasizes the importance of serving fresh food, to strengthen Pranic energy in the body. Nidra focuses on quality sleep to balance the elements of Tri Dosha in the body. Brahmacharya puts forward sexual control and knowledge nutrition towards Ojakshaya (immunity). Reviews about Tri Upastambha, are expected to contribute to efforts to build a healthy life as one of the keys to preventing Covid 19 transmission from happening again.